Retrograde drainage for duodenal stump leakage using ileal decompression tube guided by double-balloon endoscopy: a novel case report - Ryozan Naito; Nobuhiro Nakazawa; Dan Zennyoji; Takehiro Shimizu; Nobuhiro Hosoi; Takayoshi Watanabe; Ikuma Shioi; Yuta Shibasaki; Katsuya Osone; Takuhisa Okada; Takuya Shiraishi; Akihiko Sano; et al. (Surgical Case Reports, 2024)
Abstract Background Duodenal stump leakage is a serious post-gastrectomy complication, and there have been no reports on endoscopic drainage. Case presentation We report a case of duodenal stump leakage after laparoscopic gastrectomy with Roux-en-Y reconstruction in a 68-year-old man. First-line conservative management was ineffective. Reoperation was performed because of severe abdominal pain and increased ascites. After reoperation, duodenal stump leakage recurred with bleeding from the anterior superior pancreaticoduodenal artery. Coil embolization and pigtail catheter insertion were performed. Furthermore, we retrogradely inserted an ileal tube for tube decompression near the duodenal stump using double-balloon endoscopy for effective drainage. After tube insertion, duodenal stump leakage decreased; on the 47th primary postoperative day, the patient was discharged. The primary postoperative course was uneventful after 1 year and 9 months of follow-up. Conclusions This is the first successful case of duodenal stump leakage treated with retrograde decompression tube insertion near the duodenal stump using double-balloon endoscopy.